2020
DOI: 10.1038/s41415-020-1794-1
|View full text |Cite|
|
Sign up to set email alerts
|

Povidone iodine gargle and mouthwash

Abstract: 30 and 60 seconds treatment exposure under both clean and dirty conditions. In contrast, when PVP-I was tested at 1:2 dilution a >4 log10 kill at 15 seconds and >5 log10 kill at 30 and 60 seconds in comparison to control was seen in both clean and dirty. Dental practice poses a potential risk of COVID-19 cross-infection among patients, dentists and their assistants through direct exposure to saliva and indirect contact through contaminated instruments. 3 Several associations, including the Australian Dental As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 3 publications
5
23
0
1
Order By: Relevance
“…Gargle and mouth rinse with solutions containing PVP-I at 1% achieved a virucidal activity higher than 99.99%, which corresponds to a reduction of virus load greater than 4 log 10 , after 30 s of contact ( Anderson et al 2020 ). These results are in accordance with those of Hassandarvish et al (2020) , who concluded that PVP-I 1% achieved a more than 5 log 10 reduction in the virus titers after 15, 30, and 60 s of treatment. Applying 0.5% PVP-I for 15 s reduces the SARS-CoV-2 load by 4 log 10 , whereas application for 30 or 60 s reduces the load by more than 5 log 10 ( Hassandarvish et al 2020 ).…”
Section: Mouth Rinse Reagents With In Vitro or In Vivo Anti–sars-cov-supporting
confidence: 93%
“…Gargle and mouth rinse with solutions containing PVP-I at 1% achieved a virucidal activity higher than 99.99%, which corresponds to a reduction of virus load greater than 4 log 10 , after 30 s of contact ( Anderson et al 2020 ). These results are in accordance with those of Hassandarvish et al (2020) , who concluded that PVP-I 1% achieved a more than 5 log 10 reduction in the virus titers after 15, 30, and 60 s of treatment. Applying 0.5% PVP-I for 15 s reduces the SARS-CoV-2 load by 4 log 10 , whereas application for 30 or 60 s reduces the load by more than 5 log 10 ( Hassandarvish et al 2020 ).…”
Section: Mouth Rinse Reagents With In Vitro or In Vivo Anti–sars-cov-supporting
confidence: 93%
“…We previously reported these findings in abbreviated form. 27 In summary, the PVP-I product was tested at 15, 30 and 60 seconds and demonstrated ≥4 log10 reduction of SARS-CoV-2 titres (corresponding to a ≥99.99% kill rate) for all contact times, under both clean and dirty conditions. This meets the ECHA standards for disinfectant efficacy, indicating its potent and rapid virucidal activity.…”
Section: Cytotoxicitymentioning
confidence: 91%
“…A one-off participation fee of £250 will be offered to each contractor and in addition, a flat fee of £8.27 will be paid per immunisation. 3 NHS Education for Scotland is developing learning resources to support delivery of the flu vaccination programme. This is in line with the guidance from the General Dental Council that dental professionals must be trained and competent for all skills and treatment that they undertake.…”
Section: K S Fakhruddin Sharjah Uae; H C Ngo Perth Australia;mentioning
confidence: 99%
“…This is in line with the guidance from the General Dental Council that dental professionals must be trained and competent for all skills and treatment that they undertake. 3 Indemnity cover for dentists will be provided by the Scottish Government. Other members of the dental team will not be allowed to deliver vaccinations.…”
Section: K S Fakhruddin Sharjah Uae; H C Ngo Perth Australia;mentioning
confidence: 99%
See 1 more Smart Citation